(untitled) (International relations and international law Journal, 2019)
The traditional state-centrist system of international relations, based on the principle of state sovereignty and the concept of the power balance, gives way to a global multi-level interaction system, one example of which is the activity of the European Union. The changing landscape of world geopolitics dictates new trends in the development of the European Union, the provision of energy security of which is becoming increasingly important. Considering the energy policy of the European Union, the authors distinguish between different stages in the formation of a unified energy strategy. Currently, there is a trend of increasing economic competition in the global energy market, which requires constant regulation of the political course of countries. The EU countries, guided by the need to ensure energy security, form all-Union and national energy policies. The EU’s common energy policy, the priorities of which are to some extent correlated with national priorities in the designated area, focuses on a number of issues, including the search for reliable sources of energy supply, diversification of hydrocarbon raw materials transportation routes, energy efficiency and the development of renewable energy production, development of new technologies and energy security. Key words: European Union, energy policy, energy security.